2022
DOI: 10.5334/bc.224
|View full text |Cite
|
Sign up to set email alerts
|

The gendering of energy household labour

Abstract: Gender considerations, such as the division of household labour and the coordination of everyday household practices, are important for the energy transition of households. Household labour involves everyday practices (e.g. cooking, laundry and caring for others) and practices of energy household labour (e.g. managing digital technologies and energy systems). Emerging smart energy technologies require energy flexibility and efficiency, thereby introducing new forms of household labour can have implications for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
0
3
0
1
Order By: Relevance
“…Nichtsdestotrotz hat das Zusammenbringen von Gender-und Energieforschung einen erkenntnistheoretischen Mehrwert, wie eine Reihe jüngerer Arbeiten mit interdisziplinärem Hintergrund zeigen. Ausgehend von den Energieflüssen im Zuhause geraten die konkreten (Care-)Praktiken machtvoller Subjektivierungen in den Blick, die zu einer (Re-)Produktion vergeschlechtlichter Zuschreibungen beitragen (Aagaard, 2023;Aggeli et al, 2022;Khalid und Razem, 2022, Petrova und Simcock, 2021Mechlenborg und Gram-Hanssen, 2020). Wie Saska Petrova und Neil Simcock in ihrer Studie zu Energiearmut in Polen, Griechenland und Tschechien demonstrieren, sind Frauen* demnach stärker in die alltäglichen Routinen und Strategien involviert, die das politische und individuelle Ziel einer Reduktion des Energieverbrauchs verfolgen.…”
Section: Energiefeld I: Das Zuhauseunclassified
“…Nichtsdestotrotz hat das Zusammenbringen von Gender-und Energieforschung einen erkenntnistheoretischen Mehrwert, wie eine Reihe jüngerer Arbeiten mit interdisziplinärem Hintergrund zeigen. Ausgehend von den Energieflüssen im Zuhause geraten die konkreten (Care-)Praktiken machtvoller Subjektivierungen in den Blick, die zu einer (Re-)Produktion vergeschlechtlichter Zuschreibungen beitragen (Aagaard, 2023;Aggeli et al, 2022;Khalid und Razem, 2022, Petrova und Simcock, 2021Mechlenborg und Gram-Hanssen, 2020). Wie Saska Petrova und Neil Simcock in ihrer Studie zu Energiearmut in Polen, Griechenland und Tschechien demonstrieren, sind Frauen* demnach stärker in die alltäglichen Routinen und Strategien involviert, die das politische und individuelle Ziel einer Reduktion des Energieverbrauchs verfolgen.…”
Section: Energiefeld I: Das Zuhauseunclassified
“…Gender issues are also present when additional coordination and change of practices is needed to deal with new EE technologies. Studies revealed that this can exacerbate gender inequalities in the division of household labor [167].…”
Section: Towards a Comprehensive Influences' Framework On Decision-ma...mentioning
confidence: 99%
“…For example, men tend to be the main users of energy use and consumption and prefer apps for using energy systems, whereas women increasingly prefer directly installed devices, such as batteries. Energy use as well as competence in energy issues also differentiates by age, education level, local origins, and financial resources, and thus is essential to include in the systematics around energy advice, climate change mitigation, and sustainability issues (Aggeli et al, 2022).…”
Section: ____________________________________________________________...mentioning
confidence: 99%
“…Since energy consultation tends to be staffed by men, self-reflection by people in consultation and in key positions can be helpful, for example, to show that the perspectives of male consultants differ from the realities of life of many women in households who, for example, perform household chores such as cooking or cleaning, look after children and care for relatives. Energy use in households differs not only due to gender aspects of unpaid work, but also due to cultural differences-examples include behaviors related to cooking, gathering, or heating settings (Aggeli et al, 2022). In Norway, for example, it was common in the 1990s for the entire living area to be heated, whereas in Japan only one room tended to be heated, which inevitably had a major impact on energy consumption per household (Wilhite et al, 1996).…”
Section: ____________________________________________________________...mentioning
confidence: 99%